The impact of recuperation with static stretching in flexibility and agility with and without ball of young soccer players - Sermaxhaj, S.; Arifi, F.; Bahtiri, A.; Alaj, I. (Acta Kinesiologica, 2017)
Recuperation at the end of the training session is extremely important for soccer players. Activities as running with slow tempo and static stretching are typical for this part. Lately the application of static stretching has sparked debates in the science of sport and medicine. The purpose of this research was the affect of static stretching during the recuperation phase in flexibility and agility of young soccer players. The research was conducted between August and November 2015 with a sample of 24 players 13.9±0.5 years (range 13-15 years) divided into control and experimental groups. At first step that was taken was the measurement of the body height 168.4±8.5 cm (Martin`s anthropometer), and the body weight 52.9±8.5 kg (In body 720) and motoric performance flexibility (Sit and Reach test), agility performance (20m zig-zag running with and without ball). Both groups have realized the regular training session 3 times a week from August to November 2015, while the experimental group (unlike the control group), except the regular training during this period they conducted the experimental program which includes 17 static stretching exercises realized at the end of the training session. After the end of the experimental program both groups underwent the final measurements. Results analysis of variance (ANOVA) have shown that static stretching exercises applied at the end of the training session have found no statistically significant differences in any of the variables of flexibility and agility performance between the control and experimental groups of young soccer players (13-15 year old range). The level of significant is p<.05.